ANALISIS TINDAK TUTUR BERBASIS KORPUS PADA TAGAR TOLAK OMNIBUS LAW - Devi Ambarwati Puspitasari; Indah Okitasari (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2021)
ABSTRACT The purpose of this study is to find out the discursive portrayal of the hashtag “tolakomnibuslaw” on Twitter, which reveals rejection of the Job Creation Law by applying the synergy of linguistic corpus method and illocutionary speech act analysis. The data of this research is a corpus based taken from the utterances of Twitter users who use the hashtag of Omnibus Law Rejection (#tolakomnibuslaw) on October 8, 2020. Word lists and collocations analysis are utilized to see patterns of the hashtag used by people in expressing rejection of the Job Creation Law. Concordance is used to lean more the analysis of speech acts and study the data. The result show that there are 38 styles of the hashtag use. Most of them is the use of noun behind the hashtag “tolakomnibuslaw”. In addition, there are also five common topic hashtags included the hashtag “tolakomnibuslaw”. From the perspective of speech acts, there are five types of speech acts that appear and are dominated by assertive speech and forms of criticism against government effort. Keywords: linguistic corpus; social media; speech acts